2011
DOI: 10.1152/ajplung.00322.2010
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 and force regulation in porcine airway smooth muscle

Abstract: We recently demonstrated the presence of caveolae in human airway smooth muscle (ASM) and the contribution of caveolin-1 to intracellular calcium ([Ca 2ϩ ]i) regulation. In the present study, we tested the hypothesis that caveolin-1 regulates ASM contractility. We examined the role of caveolins in force regulation of porcine ASM under control conditions as well as TNF-␣-induced airway inflammation. In porcine ASM strips, exposure to 10 mM methyl-␤-cyclodextrin (CD) or 5 M of the caveolin-1 specific scaffoldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…PDE5 activity was also cross regulated by contractile agonist via PKC-mediated inhibition of protein phosphatase 1, leading to augmentation of PDE5 activity and inhibition of cGMP levels (29). PDE5 is specific for the degradation of cGMP and has no effect on the degradation of cAMP (6,9,27,44).…”
Section: Discussionmentioning
confidence: 99%
“…PDE5 activity was also cross regulated by contractile agonist via PKC-mediated inhibition of protein phosphatase 1, leading to augmentation of PDE5 activity and inhibition of cGMP levels (29). PDE5 is specific for the degradation of cGMP and has no effect on the degradation of cAMP (6,9,27,44).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we and others have previously demonstrated in vitro that the plasma membrane of human ASM cells contain caveolae (flask-shaped invaginations) that express the constituent scaffolding proteins caveolin-1 and -2 (but not caveolin-3) (15,17,41). Importantly, caveolae harbor plasma membrane proteins involved in regulation of [Ca 2ϩ ] i as well as force (17,41,48) and may thus be key regulators of ASM contractility. Indeed, we previously demonstrated that reduced caveolin-1 expression decreases ASM [Ca 2ϩ ] i and contractility (46,48), whereas proinflammatory cytokines such as TNF-␣ and IL-13 increase caveolin-1 expression, which in turn contributes to the enhanced [Ca 2ϩ ] i response of human ASM during inflammation (46).…”
mentioning
confidence: 88%
“…Importantly, caveolae harbor plasma membrane proteins involved in regulation of [Ca 2ϩ ] i as well as force (17,41,48) and may thus be key regulators of ASM contractility. Indeed, we previously demonstrated that reduced caveolin-1 expression decreases ASM [Ca 2ϩ ] i and contractility (46,48), whereas proinflammatory cytokines such as TNF-␣ and IL-13 increase caveolin-1 expression, which in turn contributes to the enhanced [Ca 2ϩ ] i response of human ASM during inflammation (46). Separately, other investigators have demonstrated that suppression of caveolin-1 is associated with a proliferative ASM cell phenotype (16,22), another key component of asthma.…”
mentioning
confidence: 99%
“…While patient identifiers are not retained with the samples, medical histories are used to select samples from female non-smokers without other significant chronic airway disease such as asthma. ASM cells were isolated and cultured using previously established procedures [13,[22][23][24][25]. Briefly, smooth muscle from lung tissues was dissected after the epithelium was removed by mild abrasions.…”
Section: Isolation Of Human Asm Cellsmentioning
confidence: 99%